2018
DOI: 10.1124/jpet.118.251199
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT2A Receptor (5-HT2AR) Regulates Impulsive Action and Cocaine Cue Reactivity in Male Sprague-Dawley Rats

Abstract: Impulsivity and the attentional orienting response to cocaineassociated cues (cue reactivity) promote relapse in cocaine-use disorder (CUD). A time-dependent escalation of cue reactivity (incubation) occurs during extended, forced abstinence from cocaine self-administration in rats. The investigational serotonin (5-HT) 5-HT 2A receptor (5-HT 2A R) antagonist/inverse agonist M100907 suppresses impulsive action, or the inability to withhold premature responses, and cocaine-seeking behaviors. The present preclini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 71 publications
2
24
0
Order By: Relevance
“…Dunnett’s multiple comparisons test demonstrated that pimavanserin restricted binge intake at 0.3 mg/kg ( p < 0.001), 1.0 mg/kg ( p < 0.001), and 3.0 mg/kg ( p < 0.001) compared to vehicle administration (Figure 2B). This lack of dose-dependent responding is consistent with other studies that have demonstrated that 5-HT 2A R antagonists often exhibit flat or very narrow dose-response curves on behavioral analyses (Vanover et al, 2006; Nic Dhonnchadha et al, 2009; Anastasio et al, 2011; Sholler et al, 2018). Finally, a repeated measures one-way ANOVA demonstrated a main effect of pimavanserin on weight gain associated with HFF exposure in the combined analyses of Cohort 1 ( n = 16) and Cohort 3 ( n = 16) ( F 3,93 = 12.37; p < 0.001).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Dunnett’s multiple comparisons test demonstrated that pimavanserin restricted binge intake at 0.3 mg/kg ( p < 0.001), 1.0 mg/kg ( p < 0.001), and 3.0 mg/kg ( p < 0.001) compared to vehicle administration (Figure 2B). This lack of dose-dependent responding is consistent with other studies that have demonstrated that 5-HT 2A R antagonists often exhibit flat or very narrow dose-response curves on behavioral analyses (Vanover et al, 2006; Nic Dhonnchadha et al, 2009; Anastasio et al, 2011; Sholler et al, 2018). Finally, a repeated measures one-way ANOVA demonstrated a main effect of pimavanserin on weight gain associated with HFF exposure in the combined analyses of Cohort 1 ( n = 16) and Cohort 3 ( n = 16) ( F 3,93 = 12.37; p < 0.001).…”
Section: Resultssupporting
confidence: 91%
“…Pimavanserin and lorcaserin were injected 30 and 15 min prior to behavioral testing, respectively. Doses, routes of administration, and pretreatment times for single administration studies were chosen based on published (Neelakantan et al, 2017; Sholler et al, 2018) studies within our laboratory that suggested these dose ranges affect reward-related behaviors. Doses for the combined administration study were chosen based on the results of the single administration studies (i.e., the lowest dose of drug that decreased binge intake was used).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to 5-HT, several studies support a role of both 5-HT2A and 5-HT2C receptors in impulsive behavior. For example, 5-HT2A receptor expression in the mPFC was higher in high compared with low impulsive animals (170). Further, activation of 5-HT2A receptors induced behavioral impulsivity, while blockade of 5-HT2A receptors inhibited behavioral impulsivity (170, 171).…”
Section: Pharmacological Targets To Treat Psychostimulant-induced Cogmentioning
confidence: 99%
“…For example, 5-HT2A receptor expression in the mPFC was higher in high compared with low impulsive animals (170). Further, activation of 5-HT2A receptors induced behavioral impulsivity, while blockade of 5-HT2A receptors inhibited behavioral impulsivity (170, 171). Moreover, 5-HT2A receptor activation in the OFC induced decisional impulsivity (172).…”
Section: Pharmacological Targets To Treat Psychostimulant-induced Cogmentioning
confidence: 99%
“…There is mounting evidence that serotonin (5-HT) neurotransmission through the 5-HT 2A receptor (5-HT 2A R) controls neural mechanisms underlying relapse-related behavioral vulnerability to cocaine, including both impulsivity and cue reactivity (for reviews) (6,7). In preclinical models, selective 5-HT 2A R antagonists administered systemically consistently reduce impulsivity and cue-primed drug seeking (24)(25)(26)(27)(28)(29). In particular, pharmacological and genetic association studies implicate 5-HT 2A R regulation of impulsive choice (30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%